Genetic Diversity of Cultivated Lentil (Lens culinaris Medik.) and Its Relation to the World's Agro-ecological Zones - Khazaei, Hamid; Caron, Carolyn T.; Fedoruk, Michael; Diapari, Marwan; Vandenberg, Albert; Coyne, Clarice J.; McGee, Rebecca; Bett, Kirstin E. (Frontiers in Plant Science, 2016)
Assessment of genetic diversity and population structure of germplasm collections plays a critical role in supporting conservation and crop genetic enhancement strategies. We used a cultivated lentil (Lens culinaris Medik.) collection consisting of 352 accessions originating from 54 diverse countries to estimate genetic diversity and genetic structure using 1194 polymorphic single nucleotide polymorphism (SNP) markers which span the lentil genome. Using principal coordinate analysis, population structure analysis and UPGMA cluster analysis, the accessions were categorized into three major groups that prominently reflected geographical origin (world’s agro-ecological zones). The three clusters complemented the origins, pedigrees and breeding histories of the germplasm. The three groups were a) South Asia (sub-tropical savannah), b) Mediterranean and c) northern temperate. Based on the results from this study, it is also clear that breeding programs still have considerable genetic diversity to mine within the cultivated lentil, however, surveyed South Asian and Canadian germplasm revealed narrow genetic diversity.